Developing a case-based e-book for office communication: Enhancing critical thinking and practical skills - Panduwinata, Lifa Farida; Wulandari, Ruri Nurul Aeni; Puspasari, Durinda; Puspasari, Durinta; Wati, Andy Prasetyo (Indonesian Journal of Educational Development (IJED), 2025)
This research aims to produce a product in the form of a case method-based office communication e-book that meets the requirements of validity and usability. Novelty in research emphasizes a unique, contemporary, and specific approach to training students to communicate effectively in the office, utilizing books integrated with technology and a case-based learning approach. This research is a development study utilizing a 4-D model. The instruments used to measure the feasibility and practicality of this textbook include validation sheets and student response questionnaires. The results of data analysis show that, according to the expert's assessment, both in terms of material, language, and graphics, it is highly feasible, with an average feasibility of 92.10% and an average score of 90.2% among student responses. Based on these results, this case method-based office communication e-book is feasible and can be used in classroom learning. Therefore, the implications of developing e-books in office communication emphasize the possibility for lecturers and students to learn more quickly, flexibly, and contextually, so that students can apply concepts from office communication to face the demands of a very dynamic work environment.